Life in a pueblo - Bishop, Amanda; Kalman, Bobbie 1947- (New York : Crabtree Pub. Co., 2003)
Photographs and text explore how pueblos were built and the daily lives of the people who lived in these communal adobe dwellings, including their spiritual beliefs.
Includes index
NC1050L
Keywords: Pueblos -- Juvenile literature; Pueblo Indians -- Dwellings; Indians of North America -- Southwest, New